STRATEGI IBU MENANAMKAN PENDIDIKAN KARAKTER DALAM LINGKUNGAN KELUARGA - Syarifah Fauzi’ah (Institut Agama Islam Negeri (IAIN) Bone-Indonesia, 2017)
This paper aims to understand the mother's strategy in instilling character education in the family environment. Family environment is the first and main educational institution for children to get knowledge especially related to the value of knowledge or character education. This paper, it is understood that the position of women in the Islamic view is glorious. As proof of her noble position of the mother in Islamic teaching, a mother is entitled to devotion of a child as much as three times more than the father. Glory was also pointed out that heaven lies at the feet of mother even the pleasure of Allah depends on the parents, especially mothers.Besides, a mother plays crucial role in shaping the character of children. To perform such a noble task, a mother can do things like: giving a child a good name, maximizing children's brain development, training independence in the House, communicating healthy with children and making nature as a school for children.